Supernova 2010ev : a reddened high velocity gradient type Ia supernova - Gutiérrez, Claudia P. (2016)
Aims. We present and study the spectroscopic and photometric evolution of the type Ia supernova (SN Ia) 2010ev. Methods. We obtain and analyze multi-band optical light curves and optical/near-infrared spectroscopy at low and medium resolution spanning from −7 days to +300 days from the B-band maximum. Results. A photometric analysis shows that SN 2010ev is a SN Ia of normal brightness with a light curve shape of ∆m15(B) = 1.12 ± 0.02 and a stretch s = 0.94 ± 0.01 suffering significant reddening. From photometric and spectroscopic analysis, we deduce a color excess of E(B − V) = 0.25 ± 0.05 and a reddening law of Rv = 1.54 ± 0.65. Spectroscopically, SN 2010ev belongs to the broad-line SN Ia group, showing stronger than average Siii λ6355 absorption features. We also find that SN 2010ev is a high-velocity gradient SN, with ˙vSi = 164 ± 7 km s−1 d −1 . The photometric and spectral comparison with other supernovae shows that SN 2010ev has similar colors and velocities to SN 2002bo and SN 2002dj. The analysis of the nebular spectra indicates that the [Fe ii] λ7155 and [Ni ii] λ7378 lines are redshifted, as expected for a high velocity gradient supernova. All these common intrinsic and extrinsic properties of the high velocity gradient (HVG) group are different from the low velocity gradient (LVG) normal SN Ia population and suggest significant variety in SN Ia explosions